Stress and resilience in nursing students from two public universities in the state of São Paulo - Fernando Oliveira de Souza; Rodrigo Marques da Silva; Ana Lúcia Siqueira Costa; Fernanda Carneiro Mussi; Carla Chiste Tomazoli Santos; Osmar Pereira dos Santos (Universidade Federal de Santa Maria, 2020)
Objective: to verify the relationship between stress and resilience in nursing students from two public universities in the state of São Paulo. Methods: cross-sectional study conducted in March 2016 with 117 nursing students. A form for academic and demographic characterization, the instrument for Assessment of Stress in Nursing Students, and the Wagnild and Young's Resilience Scale were applied. Data were analyzed in the Statistical Package for Social Sciences, version 10.0. Results: there was a predominance of students with medium stress level. Time management and theoretical activities represented a high level of stress for 23.9% and 20.5% of the nursing students who were analyzed. From the sample, 11.1% had very high stress related to the environment. Resilience levels were reduced (51%). There was no significant correlation between stress and resilience. Conclusion: the nursing education environment has potential for the development of diseases in students, although part of them already has moderate resilience.